THE PROBLEMS OF THE ENGLISH SOCIETY THROUGH THE DEPICTION OF ARTISTIC CREATIONS OF EVELYN WAUGH - Nayimova Gavkhar Zokir qizi (Scholar Express Journal, 2022)
This article is devoted to exploration how his satirical novels play with dominant structures of rationality and challenges the ways in which everybody comes across in the society in that times. In this chapter we examined two main aspects of Evelyn Waugh’s textual practice: namely his experiment with literary form and his treatment of what one might consider social topics.
Keywords: Caricature; Grotesque; Sensuality; Immaturity